2023
DOI: 10.1101/2023.09.15.558029
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Carvedilol suppresses ryanodine receptor-dependent Ca2+bursts in human neurons bearingPSEN1variants found in early onset Alzheimer’s disease

Atsushi Hori,
Tomohiko Ai,
Takashi Hato
et al.

Abstract: Seizures are increasingly being recognized as the hallmark of Alzheimer′s disease (AD). Neuronal hyperactivity can be a consequence of neuronal damage caused by abnormal amyloid Aβ depositions. However, it can also be a cell-autonomous phenomenon causing AD by Aβ-independent mechanisms. Indeed, various studies using animal models showed that Ca2+ releases from the endoplasmic reticulum (ER) via type 1 inositol triphosphate receptors (InsP3R1s) and ryanodine receptors (RyRs). To investigate which is the main pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
1
0
0
Order By: Relevance
“…We also found that the FAD iPSCs were hyper-sensitive to GSI, leading to further reduction in ATP levels. This suggests that the A246E and L286V PSEN1 mutations behave like partial loss-of-function alleles in iPSCs, according with recent biochemical studies [70,71] . Partial PSEN1 loss-of-function could promote the accumulation of the C99 fragment, which is known to be toxic "inside cells" [71] , prevents normal cleavage and/or expression of Notch [63,64] , and/or perturbs MAM transport [72] .…”
Section: Discussionsupporting
confidence: 57%
“…We also found that the FAD iPSCs were hyper-sensitive to GSI, leading to further reduction in ATP levels. This suggests that the A246E and L286V PSEN1 mutations behave like partial loss-of-function alleles in iPSCs, according with recent biochemical studies [70,71] . Partial PSEN1 loss-of-function could promote the accumulation of the C99 fragment, which is known to be toxic "inside cells" [71] , prevents normal cleavage and/or expression of Notch [63,64] , and/or perturbs MAM transport [72] .…”
Section: Discussionsupporting
confidence: 57%